Variance in Transfer of training in Manufacturing and Service Sectors - DOSS, D ARMSTRONG (The journal of contemporary issues in business and government, 2021)
Transfer of training is becoming more conspicuous and very vital from the organisation point of view there is mounting requirement to ascertain the methods to validate its accomplishment. Employee’s performance is an essential dimension from organisational and industry perspective. The ways and means by which the transfer of training affects job satisfaction and organisation commitment across manufacturing and service sectors are envisaged here. In this research Learning transfer system inventory ( LTSI ) , Person Organisational fit , person Ability fit , Organisational commitment and job satisfaction practiced in manufacturing and service industries are analysed. As a positive transfer of training leads to the growth and development of the organisation and its workforce the tangible outcomes related to transfer of training are analysed in manufacturing and service industries.